STRATEGI PUBLIC RELATIONS MYKO HOTEL & CONVENTION CENTER MAKASSAR DALAM MENYELESAIKAN KRISIS PUBLIK - Citra Ayu Mandiri; Muhammad Iqbal Sultan; Sitti Murniati Mukhtar (KAREBA : Jurnal Ilmu Komunikasi, 2017)
ABSTRACT The purpose of this research is (1) To know the public relations strategy of MYKO Hotel & Convention Center Makassar in solving public crisis; (2) To know what factors support the Public Relations of MYKO Hotel & Convention Center Makassar in solving the public crisis. This type of research uses descriptive qualitative research method by presenting data in the form of narrative descriptions, words, phrases, opinions and ideas collected by researchers from various sources. Researchers obtained data based on in-depth interviews with competent sources to answer the problem formulation, where the informants were selected by using purposive determination technique and through literature study based on the data received from the staff. The result of the research shows that the strategy used by PR in solving the public crisis include: conducting research on case and news, completing the licensing documents in accordance with the procedures of Makassar city government, press conference, providing services to the media, invite Makassar city government to come and see the situation of the company, set up crisis center. The supporting factors in solving the public crisis are human resources (HR), cooperation with stakeholders, infrastructure, budget, link building, development of information and communication technology, non-writing activities.